2014
DOI: 10.1108/el-12-2011-0175
|View full text |Cite
|
Sign up to set email alerts
|

Metadata quality in learning object repositories: a case study

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:198285 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 27 publications
0
48
0
1
Order By: Relevance
“…Unfortunately, these repositories are not used up to their full potential (Ochoa & Duval, 2009;Mitchell & Lutters, 2006;Dichev & Dicheva, 2012). Thousands of digital resources are created collaboratively and published online every day, and their quality control, assurance and evaluation are of paramount importance for potential users (Downes, 2007;Palavitsinis et al, 2013). OER enable forms of collaborative learning (Dillenbourg, 1999) and LORs of today can be considered as computer supported collaborative learning (CSCL) environments as they provide users tools for posting knowledge productions into a shared working space and providing tools for progressive discourse interaction between the users (Scardamalia & Bereiter, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, these repositories are not used up to their full potential (Ochoa & Duval, 2009;Mitchell & Lutters, 2006;Dichev & Dicheva, 2012). Thousands of digital resources are created collaboratively and published online every day, and their quality control, assurance and evaluation are of paramount importance for potential users (Downes, 2007;Palavitsinis et al, 2013). OER enable forms of collaborative learning (Dillenbourg, 1999) and LORs of today can be considered as computer supported collaborative learning (CSCL) environments as they provide users tools for posting knowledge productions into a shared working space and providing tools for progressive discourse interaction between the users (Scardamalia & Bereiter, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is vital to study LORs quality approaches (Clements et al, 2014) in a systematic way. Previous literature reviews on LOR quality approaches have focused on metadata quality only (Palavitsinis et al, 2013) and in the case of Atenas and Havemann (2014) have defined quality approaches quite simply as any approach which might attract users' to re-use content. However, this is the first systematic LOR quality approaches literature review which looks at quality management as a holistic approach around the repository, not only focusing on the quality instruments but also policies, standardization and pre-publication related quality approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicate that quality plays a major role in the sustainability of an OER project (Clements & Pawlowski, 2012;Cechinel et al, Tate & Hoshek, 2009). Knowing that users greatly value quality assurance, evaluation and quality control (Palavitsinis et al, 2013;Downes, 2007), the case study organizations of this research have shown evidence of their quality reviewing and filtering processes. Apart from quality, the research participants also associated cost with the sustainability of their business models.…”
Section: Resultsmentioning
confidence: 99%
“…Greatly valued by end-users, quality control starts at the creation stage of resources (Palavitsinis, Manouselis & Sánchez-Alonso, 2013;Downes, 2007). Learning object repositories (LORs) or OER platforms however face significant obstacles in ensuring resource quality (Pawlowski & Zimmermann, 2007;Pérez-Mateo, Maina, Guitert & Romero, 2011).…”
Section: Quality and User-generated Contentmentioning
confidence: 99%
See 1 more Smart Citation